Ho to Delay Labor Market Exit and Pension Claiming? - Stefan Staubli; Rafael Lalive (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Understanding labor market exit and pension claiming is central to pension reform. We study a Swiss reform delaying access to a full retirement pension by two years, from 62 to 64 years, by reducing early pensions by 3.4 % initially, then by 6.8 %, per year of early claiming. We find that increasing the full retirement age (FRA) by one year delays labor market exit by 4 to 6 months, affecting women who leave the labor force at the FRA. Increasing the FRA by one year delays claiming of retirement benefits by 6 to 8 months. Doubling the early retirement penalty, from 3.4% to 6.8%, delays pension claiming by almost 4 months but has no effect on labor market exit. Raising the FRA lowers social security benefits and social security wealth, by about 3 %. Doubling the early retirement penalty neither affect benefits nor social security wealth. An FRA that acts as a default retirement age generates strong effects on work and pension decisions.
Keywords: H55; J21; J26; 330